1976
DOI: 10.1177/00220345760550064501
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Experience in the Deciduous Dentition of Rural Guatemalan Children Ages 6 Months to 7 Years

Abstract: A study of 528 Guatemalan children indicated that caries prevalence in the deciduous dentition was twice as great as but in the permanent dentition was similar to that for US white children. This is a repeated observation for children of some preindustrial societies. Caries experience was significantly greater in boys. Until 4 years of age, caries attack was greater in the anterior segment of the oral cavity; linear enamel hypoplasia was a predisposing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
4
17
0
3
Order By: Relevance
“…In a study, Sweeney et al, found the linear hypoplasia of the primary maxillary incisors to be associated with infectious episodes which occurred early in life and with low serum vitamin A [14]. Likewise, Infante and Gillespie observed a strong correlation between the degree of linear enamel hypoplasia and the caries experience in the primary teeth of undernourished Guatemalan children [15]. Many studies have observed an association between the Early Childhood Malnutrition and enamel hypoplasia in the primary teeth by using various study designs [1].…”
Section: Discussionmentioning
confidence: 98%
“…In a study, Sweeney et al, found the linear hypoplasia of the primary maxillary incisors to be associated with infectious episodes which occurred early in life and with low serum vitamin A [14]. Likewise, Infante and Gillespie observed a strong correlation between the degree of linear enamel hypoplasia and the caries experience in the primary teeth of undernourished Guatemalan children [15]. Many studies have observed an association between the Early Childhood Malnutrition and enamel hypoplasia in the primary teeth by using various study designs [1].…”
Section: Discussionmentioning
confidence: 98%
“…Pascoe and Seow (1994) observed a similar phenomenon in Australian Aboriginal children and also found that the incidences of caries and EHP of the maxillary incisors were highly correlated. Infante and Gillespie (1976) stated that linear EHP was a predisposing factor for dental caries. In the present study, a high proportion of all deciduous maxillary central incisor caries consisted of transverse caries that were deemed to be a consequence of EHP [62.5% (5/8) in samurai children and 60.0% (6/10) in commoner children].…”
Section: Enamel Hypoplasia and Cariesmentioning
confidence: 99%
“…These include low birthweight [Fearne et al, 1990;Li et al, 1995] and chronic malnutrition [Enwonwu, 1973;Sweeney et al, 1971;Infante and Gillespie, 1974, 1976 and childhood disease Schour, 1941, 1942]. Mellanby [1937], Mellanby and Coumoulos [1944], and Coumoulos and Mellanby [1947] suggested vitamin D deficiency as an important factor, and this was confirmed in the clinical trial of vitamin D supplementation during pregnancy by Cockburn et al [1980].…”
mentioning
confidence: 99%